2014
DOI: 10.1371/journal.pone.0091713
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream Infections in Community Hospitals in the 21st Century: A Multicenter Cohort Study

Abstract: BackgroundWhile the majority of healthcare in the US is provided in community hospitals, the epidemiology and treatment of bloodstream infections in this setting is unknown.Methods and FindingsWe undertook this multicenter, retrospective cohort study to 1) describe the epidemiology of bloodstream infections (BSI) in a network of community hospitals and 2) determine risk factors for inappropriate therapy for bloodstream infections in community hospitals. 1,470 patients were identified as having a BSI in 9 commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 30 publications
6
96
1
5
Order By: Relevance
“…The 10% absolute risk reduction between groups can be considered as an important clinical effect. Previous studies 14,16 used regression techniques or different periods to assess the effects of ASP implementation, which is different from our study design; we compared different ASP strategies. Nonetheless, we conducted a retrospective cohort study and future prospective investigations -randomized controlled trials -would be important to answer whether different types of ASP strategies result in different outcomes.…”
Section: Mortality Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 10% absolute risk reduction between groups can be considered as an important clinical effect. Previous studies 14,16 used regression techniques or different periods to assess the effects of ASP implementation, which is different from our study design; we compared different ASP strategies. Nonetheless, we conducted a retrospective cohort study and future prospective investigations -randomized controlled trials -would be important to answer whether different types of ASP strategies result in different outcomes.…”
Section: Mortality Reductionmentioning
confidence: 99%
“…Previously, a multicenter (9 hospitals) cohort study 16 showed that 206 (38%) out of 542 patients received inappropriate use of ADT. Such rate of inadequate ADT reassures why bundled strategy may have performed so many interventions to optimize antibiotics use.…”
Section: Lower Use Of Antimicrobial Drug Therapymentioning
confidence: 99%
“…Recently, CNS was recognized as etiologic agents of a wide variety of infections and was found to be the most frequent organisms isolated from blood cultures. 4,5 Staphylococcus aureus (S. aureus), a major human pathogen, and resistant strains, especially meticillin-resistant S. aureus (MRSA), play important roles in nosocomial infection. Rapid detection of S. aureus and CNS in humans is a serious challenge in clinical research.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital-acquired BSI is the third most common cause of hospital mortality in the US [1, 2] while community-onset BSI is comparable to acute myocardial infarction, stroke and major trauma in burden of illness [3, 4]. Anderson et al looked at BSI in community level hospitals in a multicenter cohort study and concluded that 1 in 3 patients with a culture confirmed BSI receives inappropriate empiric therapy [5] and in a prospective cohort study, Retamar et al found that inappropriate empiric therapy is associated with worse outcomes [6]. Therefore, providing more rapid test results for ruling in or ruling out BSI could reduce the amount of delayed treatment while also promoting antimicrobial stewardship by decreasing the use of inappropriate, ineffective or unnecessary empiric antimicrobial therapy.…”
Section: Introductionmentioning
confidence: 99%